Pendidikan Kristiani Transformatif dalam Pembentukan Moral Pada Siswa SMP Negeri di Kecamatan Tuminting Kota Manado - Yolanda Marta Lidya Samalukang; Andy. P P.P Undap; Made Astika (Peneliti.net, 2021)
The purpose of this study is to describe (1). How Transformative Christian Education in Moral Formation in Junior High School Students in Tuminting District, Manado City. (2). Supporting factors for Transformative Christian Education in Moral Formation of State Junior High School Students in Tuminting District, Manado City, (3). Constraints of Transformative Christian Education in Moral Formation of State Junior High School Students in Tuminting District, Manado City, (4). efforts to overcome the constraints of Transformative Christian Education in Moral Formation in State Junior High School Students in Tuminting District, Manado City. This study uses a qualitative method. The data collection techniques used were observation, interviews and documentation study. From the findings, the following conclusions were obtained: (1). Transformative Christian education carried out by teachers of SMP Negeri in Tuminting District is: Worship and giving material can lead students to learn from everyday life (2). This transformative Christian education is supported by the process of forming student morale due to deviations committed by students so that materials are provided that encourage students to experience spiritual change. (3). Constraints in transformative Christian education are due to the lack of a broad understanding of this approach that teachers should be co-learners (4). Teachers must develop conversational education that generates a commitment to aware, listen to, respond to, and create a connection between matter and faith From the findings, it is recommended that school principals and teachers seek and develop an understanding of transformative Christian education, as well as provide in-depth understanding to students and provide facilities to support this activity.